2018
DOI: 10.1111/1756-185x.13374
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of joint cartilage thickness in healthy children by ultrasound: An experience from a developing nation

Abstract: Measurement of joint cartilage thickness in children with MSUS and comparison with these normative values can help in better screening for joint-related disease in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
5
10
0
1
Order By: Relevance
“…In line with Spannow and Moumita's observation [7,8], our data on school aged children between age 5 to 13 suggested that the Cth declines as the age advances. Although this linear correlation is true in our study as well as other reports [7,8], it is not always the case since the measures of Cth in those preschoolaged-children and elder teens have been reported otherwise [17]. In the present study, without the very young children and older teens, we took advantage of the linear correlation and established a formula to calculate the Cth with 95% con dent interval in the knees, ankles, wrists, MCPs and PIPs joints among Taiwanese school aged girls and boys.…”
Section: Discussionsupporting
confidence: 91%
“…In line with Spannow and Moumita's observation [7,8], our data on school aged children between age 5 to 13 suggested that the Cth declines as the age advances. Although this linear correlation is true in our study as well as other reports [7,8], it is not always the case since the measures of Cth in those preschoolaged-children and elder teens have been reported otherwise [17]. In the present study, without the very young children and older teens, we took advantage of the linear correlation and established a formula to calculate the Cth with 95% con dent interval in the knees, ankles, wrists, MCPs and PIPs joints among Taiwanese school aged girls and boys.…”
Section: Discussionsupporting
confidence: 91%
“…Standard reference values provide the basis for pediatric musculoskeletal sonography had been established in a Danish study [ 7 ] and in India [ 8 ] focusing on Caucasians and multiethnic population. Their results indicated that with the growth of age, the thickness of hyaline cartilage may decline with decreasing cellular concentrate [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a cross‐sectional study including 27 diagnosed cases of JIA according to the 2001 revised International League of Associations for Rheumatology classification, aged 2‐12 years who attended the pediatric rheumatology clinic of a tertiary care hospital from June 2013 to May 2014. A group of 54 age‐ and sex‐matched healthy children were selected randomly from our previously published study cohort to compare with the cases. Two controls were selected for each case by stratified random sampling to avoid selection bias.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasound has shown to be a reliable tool in the assessment of joint cartilage thickness in rheumatic diseases . We have used ultrasonography (USG) to establish age‐ and sex‐related normal reference intervals for joint cartilage thickness in children between the ages of 2 to 12 years in our previous study . In this study we have assessed changes in cartilage thickness in the knee, ankle, and wrist joints in a pediatric population suffering from JIA.…”
Section: Introductionmentioning
confidence: 99%